Lymphovascular invasion in breast carcinoma - Norhisham, Nur Fatiha (Universiti Sains Malaysia, 2015)
Lymphovascular invasion comprising of blood vascular invasion and lymphatic vessel invasion has become one of the important existence in breast carcinoma. However, it is not clear which type of vascular invasion plays a major role in metastasis. The aims of this study were to investigate the role of lymphatic and blood vessel invasion, and lymphatic and microvessel density as prognostic biomarkers in 19 breast carcinoma patients. Immunohistochemical method was used where sections of breast carcinoma were stained with anti-D2-40 and anti-CD34 antibodies to evaluate lymphatic and blood vessel invasion respectively. Vascular invasion by immunohistochemical method was compared with vascular invasion determined by hematoxylin & eosin (H&E) staining. Vascular invasion was also assessed by correlating with clinicopathological criteria. Vascular invasion was detected in 16 (84.2%) cases; 5/16 (31.3%) were lymphatic vessel invasion, 2/16 (72.5%) were blood vessel invasion and 9/16 (56.3%) showed both lymphatic and blood vessel invasion. Intratumoral lymphatic vessel invasion was significantly associated with tumor size (p=0.029), while peritumoral lymphatic vessel invasion was associated with distant metastasis (p-0.018) and blood vessel invasion (p=0.024). These results suggest that vascular invasion in breast carcinoma predominantly occurs via lymphatic vessels and the association of lymphatic invasion with distant metastasis provides evidence for their biological importance in breast carcinoma. Hence, it is suggested that lymphatic invasion be included in clinical practices as one of the potential prognostic biomarkers of breast carcinoma.